BOLALARDA TUG’MA QIZILO’NGACH ATREZIYALARI (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Congenital esophageal atresia (TQA) in children is a congenital pathology that occurs as a result of the underdevelopment or loss of some or all parts of the esophagus. Complete or partial loss or obstruction of the esophagus can lead to severe respiratory problems in the child and requires treatment. This article will tell you in detail about congenital esophageal atresia in children and consider its causes, diagnosis, clinical indications and methods of treatment. In esophageal atresia, the upper part of the esophagus ends blindly, while the lower girl often comes into contact with the trachea. It occurs in 5% of cases with chromosomal disorders. The frequency of occurrence in the population is every 1,000, in a 1:1 ratio between males and females, types of esophageal atresia can occur.